Testing the Credibility of the Belgian Hard Currency Policy - Koen, Vincent (International Monetary Fund, 1991)
Interest rate differentials have been widely used to assess the degree of policy credibility. A problem with this measure, however, is that the relationship between the differential and credibility varies not only across maturities but also with the actual level of the exchange rate. The alternative approach used in this paper, based on the construction of rate-of-return bands, overcomes this difficulty. It is applied to Belgium, which in May 1990 hardened its exchange rate policy stance. Comparisons with other small, open European economies are carried out. Econometric evidence is provided supporting the claim that the announcement and active implementation of a tighter exchange rate link does make a difference